Locking Out Lawful Users: Fair Dealing and Anti‑Circumvention in Bill C‑32 - Craig, Carys (From "radical extremism" to "balanced copyright": Canadian copyright and the digital agenda, 2010)
Copyright has long been viewed as one of the government?s most difficult policy issues. It attracts passionate views from a wide range of stakeholders, including creators, consumers, businesses, and educators and it is the source of significant political pressure from the United States. The latest chapter in the Canadian copyright saga unfolded in June 2010 as Industry Minister Tony Clement and Canadian Heritage James Moore tabled Bill C-32, copyright reform legislation billed as providing both balance and a much-needed modernization of the law. The introduction marked the culmination of months of public discussion and internal government debate. This book represents an effort by some of Canada?s leading copyright experts to shift away from the sloganeering that has marked the debate to date by moving toward an informed analysis of Bill C-32 and the future development of Canadian copyright law. Edited by Professor Michael Geist, an internationally regarded authority on Internet and technology law, it responds to the need for non-partisan, informed analysis of Bill C-32. An exceptional group of Canadian scholars from coast-to-coast have come together to assess Canada?s plans for copyright reform and the digital agenda in this timely volume that features context for the reforms, analysis of its impact on technology, business, education, and creators, as well as a look ahead to future copyright and digital issues.